The immunopathogenesis of cow's milk protein allergy (CMPA) - Giovanna Vitaliti; Carla Cimino; Alfina Coco; Domenico Praticò; Elena Lionetti (BMC, 2012)
Abstract The most frequent symptoms among the manifestations of cow milk protein allergy (CMPA) are gastrointestinal. CMPA pathogenesis involves immunological mechanisms with participation of immunocompetent cells and production of immunoglobulin E (IgE). Nevertheless, recent studies have been focused on the description of other forms of CMPA, not-mediated by IgE reactions, mostly involving the T lymphocite immune system. Thus, in this field it is important to note how different kind of cells are involved in the immunopathogenesis of CMPA, such as antigen-specific T cells, T regulatory cells, cytokines secreted by the different T lymphocite subsets, B lymphocytes, antingen-presenting cells, mast cells, that together orchestrate the complex mechanism leading to the phenotipic expression of CMPA. The progress in the diagnosis of immunologic disorders allowed the recent literature to develop new models for immuno-mediate disorders, involving new cells (such as Treg cells) and thus allowing the acquisition of a new vision of the pathogenesis of atopic diseases. The aim of this review is to describe the immunopathogenetic aspects of CMPA in view of these new discoveries in the immunologic field, considering the immunologic pathway at the basis of both IgE- and not-IgE mediated CMPA.